Investigate the ability of moringa oleifera seeds and neem leaves as anti-fungal activity in urban drinking water - Salah Omar Abdulali, Habberrih (2022)
High-quality drinking water coming from treatment plants is susceptible to pollution and severe deterioration due to the drinking water delivery system prior to access to consumers' faucets. Water must be pure and free of any contaminants for human consumption. However, promising water treatment procedures are considerably more expensive, and many of the disinfectants now in use are toxic, making the hunt for safer organic alternatives even more important. Previous studies proved the ability of Moringa oleifera seeds and Neem leaves to treat water in the area of limiting bacterial growth and reducing water turbidity. The previous studies have not verified the ability to limit the growth of fungi in the drinking water network. For this reason, this study was carried out to choose Moringa oleifera seeds and Neem leaves to verify their ability to limit it the growth of fungi present in the drinking water distribution system. The samples were taken from a tap of local residential and public building that contains direct water from Kuantan's Semambu Water Treatment Plant. Water quality parameter were measured using Malaysian and WHO drinking water quality criteria. It was found that parameters such as colour, turbidity, and chloride were within acceptable limits in most tap water samples according to the National Drinking Water Quality Standards (NDWQS) of the Ministry of Malaysia and WHO. The residual free chlorine in the tap water of these selected areas varied from 0.05 to 1.97 mg/L, the turbidity was varied with an average of 3.8 NTU, and the taste threshold for calcium ions is 100 mg/l to 300 mg/l. The typical two fungi widespread in the tap water samples have detected which are Aspergillus sp. (73%) and Rhodotorula mucilaginosa (63%). The results confirmed that Moringa seeds, Neem leaves extract and chlorine at all concentrations had antifungal activity against the under this investigation. The most significant factors, which are dosage, time, and agitation, were selected for further evaluation of their impact on eliminating the fungi communities' growth in the drinking water using central composite design (CCD) in response surface methodology (RSM). The results for validation were between 0 % to 5.88 % in error for Rhodotorula mucilaginosa and Aspergillus sp. These findings also implied that the developed models were reliable for limit the growth of the fungi within the 94 % confidence interval. Because the seed of the Moringa oleifera and leaves of the Neem can be produced locally, its use in water treatment should be encouraged. The high expenses and health hazards connected with frequently used chemical water treatments would be reduced as a result of this. Because the process is biological, no non-treatable wastes are created, the solution is cost-effective, traditional, and easy to implement, making them ideal for rural regions.